Efektivitas Penerapan Media Pembelajaran Butterfly Trigon Dalam Model Kooperatif Tipe TSTS - Asdar; Nasrullah; Nur Putri Ramadhani Yusuf (Issues in Mathematics Education (IMED), 2022)
This research aims to determine the effectiveness of the application Butterfly Trigon learning media in the cooperative model type TSTS on mathematics learning for X grade high school students with the indicators of learning effectiveness is student learning outcomes, student activities, and student responses. This research is a quasi-experimental research with pretest and posttest control group design using cluster random sampling technique. The population of this study were X grade high school students and the research sample consisted of two groups, namely the experimental class (Treatment) with 25 students and the control class with 24 students. Student learning outcomes data obtained by giving pretest and posttest, student activity data obtained through student activity observation sheets, and student response data obtained by student response questionnaires. Data analysis used descriptive statistics and inferential statistics so in general it can be concluded that the application Butterfly Trigon learning media in the cooperative model type TSTS is effectively applied on the mathematics learning for X grade high school students.